Confirmations that were not meant to be: religion, violence and the female body in Un poison violent (2010), Corpo celeste (2011) and Kreuzweg (2014). Issue 1 (2nd January 2023) - Angeli, Silvia; Quaranta, Chiara
ABSTRACT: This article considers the representation of the adolescent female body and the relevance of corporeality in Catholicism in three Western European films, which have at their centre the religious confirmation. These are: Un poison violent ( Love Like Poison, 2010, Katell Quilléveré), Corpo celeste ( Heavenly Body, 2011, Alice Rohrwacher), and Kreuzweg ( Stations of the Cross, 2014, Dietrich Brüggemann). The sacrament of confirmation as portrayed in the three films becomes the axis around which the dynamics of adolescence (i.e., changing body, blossoming sexuality, family conflicts) unfold, opening up a space for the analysis of the interplay between female subjectivities and Catholicism's regulatory role. We look at the often-subtle violence exerted by Catholicism in an attempt to tame the female body and the ways female adolescents (re)negotiate their identity against the backdrop of religious authority. Our contention is that, in the films, the female protagonists' subtraction from the confirmation becomes a way to distance themselves from the Catholic obedient body and reaffirm their individual, embodied subjectivity. To this end, we engage with the complex relationship between Catholicism, women, and women's bodies, exploring the dichotomy between the Catholic ideal, unchangeable body and the continually-changing, desiring female bodies.